Testing a Novel Aggregated Methodology to Assess Hydrodynamic Impacts on a High-Resolution Marine Turtle Trajectory - Giovanni Quattrocchi; Andrea Cucco; Giulia Cerritelli; Resi Mencacci; Giorgia Comparetto; Daniela Sammartano; Alberto Ribotti; Paolo Luschi (Frontiers in Marine Science, 2021)
We designed a novel aggregated methodology to infer the impact of ocean motions on the movements of satellite-tracked marine turtles adopting available oceanographic observations and validated products of a numerical oceanographic forecasting system. The method was tested on an 11-months trajectory of a juvenile loggerhead turtle (LT) wandering in the Tyrrhenian Sea (Mediterranean Sea) that was reconstructed with a high-resolution GPS tracking system. The application of ad-hoc designed metrics revealed that the turtle’s route shape, ground speed and periodicities of its explained variance mimic the inertial motions of the sea, showing that this methodology is able to reveal important details on the relation between turtle movements and oceanographic features. Inertial motions were also identified in the observed trajectory of a surface drifting buoy sampling the Tyrrhenian Sea in a common period. At each sampling point of the turtle trajectory, the sea current eddy kinetic energy (EKE) and a Sea Current Impact index were computed from a validated set of high-resolution ocean modeling products and their analysis showed the relevant effects of the highly variable local sea currents mechanical action. Specifically, the metric we adopted revealed that the turtle trajectory was favorably impacted by the encountered sea current advection for about 70% of its length. The presented oceanographic techniques in conjunction with high-resolution tracking system provide a practicable approach to study marine turtle movements, leading the way to discover further insights on turtle behavior in the ocean.